The Role of Prosocial (Politicized) Identity and Prejudice in Collective Action Intentions to Help Women and Men Suffered from Domestic Violence - O.A. Ananyeva; I.S. Prusova (Социальная психология и общество)
Objective. Analysis of the relationships between prosocial identity, ambivalent prejudice, self-efficacy, and anger in intentions to participate in collective action to help women and men suffered from domestic violence. Background. Since the decriminalisation of domestic violence in Russia in 2017, researchers have noted various strategies to de-problematize domestic violence in Russian media and public opinion polls indicate the low willingness of Russians to help domestic violence survivors. A study of predictors of willingness to participate in collective action to help domestic violence survivors will help to clarify psychological mechanisms and barriers to the realisation of the prosocial potential of Russians, as well as develop recommendations for social campaigns aimed at helping violence survivors. Study design. Theoretical framework of the current study was Dual Chamber Model of Collective Action (modification of Social Identity Model of Collective Action). The study examined the relationship between prosocial (politicized) identity (i.e. identification with helping groups), ambivalent prejudice towards women and men, self-efficacy to change a situation, anger and the intentions to participate in various forms of collective action to help women and men suffered from domestic violence. Direct and indirect associations were tested using partial least squares structural equation modelling (PLS-SEM). Participants. Two Russian samples. N1 (intentions to help women) = 323 (54,8% females, 45,2% males) from 18 to 78 years old (M = 36,63; SD = 12,15), N2 (intentions to help men) = 267 (53,2% females, 46,8% males) from 18 to 64 years old (M = 35,46; SD = 10,32). Measurements. Adapted to Russian scales of the in-group identification developed by C. Leach, the ambivalent sexism and ambivalence towards men inventories by P. Glick and S. Fiske, questions measuring self-efficacy to change situation, anger, and intentions to participate in various forms of collective action to help women and men suffered from domestic violence, adapted from European Social Survey. Results. Prosocial identity makes a significant positive contribution to the intentions to help women and men suffered from DV, both directly and indirectly through self-efficacy (to help both women and men suffered from DV) and anger (to help men suffered from DV). Hostile sexism and benevolent attitudes (both towards women and men) directly undermine the willingness to engage in certain forms of prosocial collective action. Conclusions. There are significant associations between prosocial identity, self-efficacy, anger towards the situation of survivors, ambivalent prejudice and willingness to participate in various forms of collective action to help women and men suffered from domestic violence.